2006
DOI: 10.1139/g06-096
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the apple scab-resistance gene Vb

Abstract: Apple scab, caused by the fungus Venturia inaequalis, is the major production constraint in temperate zones with humid springs. Normally, its control relies on frequent and regular fungicide applications. Because this control strategy has come under increasing criticism, major efforts are being directed toward the breeding of scab-resistant apple cultivars. Modern apple breeding programs include the use of molecular markers, making it possible to combine several different scab-resistance genes in 1 apple culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…Patocchi et al (1999a) suggested two hypotheses to explain this situation; the first one is that these plants are double recombinants, and the second one is that they were wrongly classified. As reported by these authors (Patocchi et al 1999a;Gygax et al 2004;Erdin et al 2006), the presence of double recombinants is quite unlikely because of the distance of the flanking markers in coupling with Vd3. In our case, we expect a frequency of double recombinants of 0.6% and not the 3% observed.…”
Section: Linkage Mapmentioning
confidence: 58%
See 2 more Smart Citations
“…Patocchi et al (1999a) suggested two hypotheses to explain this situation; the first one is that these plants are double recombinants, and the second one is that they were wrongly classified. As reported by these authors (Patocchi et al 1999a;Gygax et al 2004;Erdin et al 2006), the presence of double recombinants is quite unlikely because of the distance of the flanking markers in coupling with Vd3. In our case, we expect a frequency of double recombinants of 0.6% and not the 3% observed.…”
Section: Linkage Mapmentioning
confidence: 58%
“…In both situations, the gene is mapped between the same markers, and the order of the markers in the map is not altered, but in the case of the exclusion of the GPI plants, the distance between Vd3 and the Vf locus was reduced from 2.9 to 1 cM. As was reported by other authors (Patocchi et al 1999a;Gygax et al 2004;Erdin et al 2006), we found difficulties determining the correct position of Vd3, as the phenotypic data were not as precise as the molecular data. During the analysis of the population 2000-012C, we classified three plants (3%) as susceptible, but the flanking marker alleles were in coupling with the resistance.…”
Section: Linkage Mapmentioning
confidence: 69%
See 1 more Smart Citation
“…In only one case, Z71981 SSR (LG15), is the approximate map position still to be determined. Some SSRs of the Hi set have already been mapped in other crosses than Fiesta × Discovery, and their map position relative to other SSRs was confirmed (Patocchi et al 2005;Gardiner et al 2006;Erdin et al 2006;Durel, unpublished).…”
Section: Accuracy Of Map Positionsmentioning
confidence: 74%
“…Firstly, the Genome Scanning Approach (GSA, Patocchi and Gessler 2003) allows efficient mapping of major genes. This procedure was successfully applied to map the apple scab resistance genes Vr2, Vm Patocchi et al 2005), and Vb (Erdin et al 2006). Secondly, the Pedigree Genotyping concept was developed , which allows the exploitation of breeding material in the assessment of marker-trait associations and in allele mining by using multiple pedigreed plant populations, which can be any combination of crosses, cultivars, and breeding lines.…”
Section: Introductionmentioning
confidence: 99%